(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Breastfeeding has been accepted as the most vital intervention for reducing infant mortality and ensuring optimal growth and development of children. Breastfeeding is also considered as the most economical and easily accessible complete nutrition for every new born child1. Poor breastfeeding practices are widespread. It is estimated that sub-optimal breastfeeding, especially non-exclusive breastfeeding in the first 6 months of life, results in 1.4 million deaths and 10% of the disease burden in children younger than 5 years of age2. Reviews of studies from developing countries showed that infants who were not breast fed were 6 to 10 times more likely to die in the first months of life than infants who are breast fed3. The World Health Organization has stated that in 2000, only 16% of mothers in Pakistan exclusively breast feed for a period of three months, as compared to other developing countries where the ratio is higher like Bangladesh (46%), India (37%), and Sri Lanka (84%)4. More than 15% of 24 lakh child deaths could be averted in India by optimal breastfeeding practices5. The key to successful breastfeeding is Information, Education and Communication (IEC) strategies aimed at behavior change6. The World Health Organization (WHO) and United Nations Children’s Fund (UNICEF) strongly recommends exclusive breastfeeding (EBF) for the first six months of life7. Variables that may influence breastfeeding include race, maternal age, maternal employment, level of education of parents, socio-economic status, insufficient milk supply, infant health problems, method of delivery, maternal interest and other related related factors8,9. Over the last decade, overwhelming scientific evidence supporting the integral role of breastfeeding in the survival, growth and development of a child, as well as the health and well-being of a mother has come to light10. Different studies were designed at national and international level to explore the knowledge, attitude and practices (kap) towards breastfeeding among postnatal mothers and factors that determine them1. Journal of Armed Forces Medical College Bangladesh Vol.11(2) 2015: 76-83